Introduction to an Economics E-Module for Teachers in the Malang Raya Economics Teachers’ Working Group as a Technology-Based Teaching Solution - Ni'matul Istiqomah; Wahjoedi; Nur Anita Yunikawati; Emma Yunika Puspasari; Nimas Candhyta Maharani; M. Yusril Naili Rizqi (Universitas Pendidikan Ganesha, 2026)
Technology is changing the world of education, especially how learning is implemented. During the COVID-19 pandemic, learning was often conducted online via virtual meeting rooms. The purpose of this community service is to familiarize the E-Module with flip mode to enhance its display. In addition, the Implementation of the Independent Curriculum (IKM) is one of the scopes in module development, in which the module has been integrated with materials in accordance with the Learning Outcomes of Phases E and F of SMA/MA. This community service uses a socialization method with the following stages: Observation and identification of partner needs; Planning PKM activities; Implementing PKM activities; Conducting evaluations; and Making PKM reports. The focus of this service is the socialization of the e-module for teachers of the Malang Raya Economics MGMP. The result of this community service is that teachers have a better understanding of the E-Module concept and can design teaching materials to support more innovative and interactive economic learning. The implementation of the E-Module provides benefits in terms of production and distribution cost efficiency, as it eliminates the need for expensive physical printing. Learning materials can be updated and disseminated instantly at no additional cost, making it an environmentally friendly solution.